An Overview on Training Conducted by Pokhara Tourism Training Centre, Pokhara - Karki, Bir Bahadur (Journal of Nepalese Business Studies, 2006)
Pokhara Tourism Training Center (PTTC) under the Council for Technical Education and Vocational Training, and Skill Development Training Center (SDTC), Pokhara Branch, under the Ministry of Labor, are conducting skill-oriented training in Pokhara. Both institutions have emphasized the short-term training. SDTC has conducted 19 different training programs and trained 4,116 people, and PTTC has conducted 21 different training and trained 2,552 people till FY 2057/ 058. PTTC offers both short and long-term training. In short term courses, 2765 participants have participated so far. In both short term and long-term courses, in total, 3,352 trainees received various kinds of training.. PTTC may focus the short-term training due to its popularity. Journal of Nepalese Business Studies Vol.1(1) 2004 pp.93-98